Factors of change towards work performance among academic and non-academic staff / Nur Aisha Nastika Paudin, Nurul Amiera Zailan and Norliza Narmila Zunaidi - Paudin, Nur Aisha Nastika; Zailan, Nurul Amiera; Zunaidi, Norliza Narmila (2012)
This study aims to examine the relationship between the factors of change such as technological change, changes in the environment and work culture towards work performance. We are focus on the impact of such changes on all of these factors. The samples of this study were given to 100 respondents consists of academic staff and non academic staff, comprising staff at UiTM Jengka, Pahang. However, there are only 40 respondents who responded to our questionnaires. The results showed a significant positive difference existed between the factors such as changes in technology factors, changes in the environment and work culture towards work performance. Proven previous studies also showed a positive difference between factors of changes and work performance. This may be due to the factors of change toward work performance may vary for each others.